Therapeutic patient education: Impact on lung function in Moroccan adult asthma patients? - Hanane El Abed; Mohammed E. A. Ragala; Hanaâ Ait-Taleb Lahsen; Mohamed C. Benjelloun; Karima Halim (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Despite the availability of effective asthma medications, the condition remains poorly controlled, making it one of the most common emergency room and physician visits each year. Appropriate asthma education programs are needed to maintain or improve optimal lung function in asthmatics. This study aimed to evaluate changes in lung function parameters in adult asthmatics before and after a structured educational intervention. METHODS AND MATERIALS: We conducted a quasi-experimental study with 157 adult asthma patients in the Pneumology Department of the Hassan II University Hospital in Fez, Morocco. The study was performed in three phases: patient recruitment and baseline data collection (March-May 2022), planning and implementation of educational sessions (June-July 2022), and lung function evaluation 3 months later (September-October 2022) after training. Sociodemographic and clinical data were collected through a questionnaire. Spirometry was also performed before education and 3 months after. All patients received a structured and collective educational intervention. Pre- and post-education results were compared using the Wilcoxon test for qualitative variables and the paired sample t-test for quantitative variables. RESULTS: There was a statistically significant improvement (P < 0.001) in pulmonary function parameters (as a percentage of the reference value): forced expiratory volume in one second (FEV1), forced vital capacity (FCV), and peak expiratory flow rate (PEFR) sequentially increased from 66.73 ± 20.84 to 70.64 ± 19.06; 74.74 ± 17.29 to 79.67 ± 16.15 and 67.51 ± 23.39 to 71.93 ± 21.57. CONCLUSIONS: Our results suggest that an educational intervention can be beneficial in reducing alterations in lung function in adult asthmatics.